Proven Delivery Models for LED Public Lighting : ESCO Delivery Model in Central and Northwestern India - Makumbe, Pedzisayi; Weyl, Debbie K.; Eil, Andrew; Li, Jie (World Bank, Washington, DC, 2016)
The project covers seven cities, encompassing nine urban local bodies: seven municipal corporations (MCs) and two urban improvement trusts (UITs). The urban local bodies are responsible for infrastructure improvements in the cities. The cities are spread across three states in central and northwestern India: Rajasthan, Madhya Pradesh, and Maharashtra. They range in size from 260,000 (Alwar) to 2.6 million (Pune), with most in the range of 300,000 to 500,000 inhabitants. Institutionally, municipalities in India are under little regulatory obligation to improve lighting quality to meet standards. India’s Code of Practice for Lighting, created in 1970 by the Bureau of Indian Standards (BIS) to establish lighting standards for categories of streets and roads, and has not been updated since 1981. Further, as USAID report from 2010 notes, ‘since these guidelines are not enforced by any regulatory authority, it is common for municipalities to be unaware of the standards, and many fail to comply.’ Consequently, project upgrades are not driven by regulatory compliance but by municipalities’ initiative to save operating funds on electricity and maintenance, and to improve street lighting quality.